Optical Metamaterials by Block Copolymer Self-Assembly - Salvatore, Stefano (Springer, 2015)
Metamaterials are artificially designed materials engineered to acquire their properties by their specific structure rather than their composition. They are considered a major scientific breakthrough and have attracted enormous attention over the past decade. The major challenge in obtaining an optical metamaterial active at visible frequencies is the fabrication of complex continuous metallic structures with nano metric features.